The Relationship Between Mother’s Knowledge About Nutrition Fulfillment And The Nutritional Status Of Children Aged 1-3 Years Old In Posyandu Melati RW 006 Kelurahan Palmeriam During COVID-19 Pandemic And The Review According To Islamic Perspective - Vasha Annisa Hidayat; Rika Yuliwulandari; Firman Arifandi (Junior Medical Journal, 2023)
Background: COVID-19 pandemic had an impact on activities in Posyandu. This has been proven by the decreased number of visits by the Posyandu cadres and the visitors. One of the activities that Posyandu held is nutrition services. Nutrition is various substances that are obtained from food and are important for metabolic processes. The nutritional status needs to get more attention from parents because malnutrition in childhood can cause permanent damage. The purpose of this study is to determine the relationship between mother’s knowledge about nutrition fulfillment and the nutritional status of children aged 1-3 years old in Posyandu Melati RW 006 Kelurahan Palmeriam during COVID-19 pandemic and the review according to Islamic perspective. Methods: This study uses an analytic correlational survey with cross-sectional approach as the methods. The method that was used to determine the sample in this study is total sampling with a total sample of 56 respondents. Data was collected by filling out questionnaires regarding nutritional fulfillment by mothers and weighing children aged 1-3 years old at Posyandu Melati RW 006 Kelurahan Palmeriam. Chi-Square test is used to analyze the data. Results: The results showed that most of the mothers have good knowledge about nutritional fulfillment (55.4%) and most of the children have a good nutritional status (48.2%) and the p value: 0.037 is obtained in this test.Conclusion: There is a relationship between the mother’s knowledge about nutrition fulfilment and the nutritional status of children aged 1-3 years old in Posyandu Melati RW 006 Kelurahan Palmeriam during COVID-19 pandemic.